2014
DOI: 10.1111/cdev.12223
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Maltreated and Nonmaltreated Children's Transgression Disclosures: Narrative Practice Rapport Building and a Putative Confession

Abstract: This study tested the effects of narrative practice rapport building (asking open-ended questions about a neutral event) and a putative confession (telling the child an adult “told me everything that happened and he wants you to tell the truth”) on 4- to 9-year-old maltreated and nonmaltreated children's reports of an interaction with a stranger who asked them to keep toy breakage a secret (N = 264). Only one-third of children who received no interview manipulations disclosed breakage; in response to a putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 85 publications
9
100
0
Order By: Relevance
“…The putative confession involves an interviewer informing a child that a known suspect “told me everything that happened and he wants you to tell the truth” (Lyon et al, 2014, pp. 1756).…”
Section: Putative Confessionmentioning
confidence: 99%
See 2 more Smart Citations
“…The putative confession involves an interviewer informing a child that a known suspect “told me everything that happened and he wants you to tell the truth” (Lyon et al, 2014, pp. 1756).…”
Section: Putative Confessionmentioning
confidence: 99%
“…Because the putative confession does not explicitly suggest what happened, it is not overtly suggestive. Evidence indicates that its inclusion at the start of an interview increases children’s willingness to disclose transgressions in which the children were implicated, with no increase in false reports if no transgression occurred (Lyon et al, 2014; Rush et al, 2015; Stolzenberg et al, 2016). …”
Section: Putative Confessionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across age, all children required more pressure—in the form of negative feedback—to agree with the negative false details. Children’s positivity biases (Carrick & Quas, 2006; Samuels & Taylor, 1994) and reluctance to discuss wrongdoing (Lyon et al, 2014; Talwar & Lee, 2002) may underlie this trend. Of interest, valence did not further interact with whether the child or confederate was implicated to affect children’s accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that children are less likely to disclose transgressions implicating themselves or someone close to them as they become older (Bottoms et al, 2002; Lyon et al, 2014; Talwar & Lee, 2002), a trend likely driven both by their desire to avoid punishment (Last & Aharoni-Etzioni, 1995) and by their emerging understanding of false beliefs which allows them to more skillfully conceal a transgression (Talwar, Gordon, & Lee, 2007). Of course, in these studies, the transgression actually occurred.…”
Section: Developmental Levelmentioning
confidence: 99%